Enhancing persistence on mastery tasks among young preschool children by Implementing the “I Can” mastery motivation classroom program - Shazia Iqbal Hashmi; Chua, Bee Seok; Murnizam Hj Halik (Debrecen University Press, 2017)
Task persistence plays important role in school readiness and helps to enhance young children’s cognitive development and academic skills; thus, designing and implementing programs to enhance it is vital. The objective of the present research was to assess the effectiveness of the “I Can” mastery motivation classroom program in enhancing young children’s persistence on mastery tasks. Altogether, forty-four (n = 44) children between the ages of two to three years selected from three kindergartens in Malaysia participated in the research, which was conducted by using a randomized pretest and posttest experimental-control group design. Persistence on three mastery tasks and mastery pleasure were assessed by using the Individualized Assessment of Mastery Motivation manual. The experimental group (n = 25) was exposed to the “I Can” mastery motivation classroom program, while the control group (n = 19) attended regular classroom lessons. There was a significant gain score difference between the experimental and control groups on task persistence for puzzles but not for shape sorters, cause and effect toys, and mastery pleasure. Thus, the program was effective in enhancing persistence on some mastery tasks. The content and findings of the intervention should help policy makers understand this important aspect of early childhood education.